2012
DOI: 10.1007/s10616-012-9506-6
|View full text |Cite
|
Sign up to set email alerts
|

Grape seeds proanthocyanidin extract as a hepatic-reno-protective agent against gibberellic acid induced oxidative stress and cellular alterations

Abstract: The present study aims to investigate the heptonephro-protective effect of grape seeds proanthocyanidin extract (GSPE) against the risks induced by gibberellic acid (GA3) in male rats. The results recorded that GA3 caused a significant increase in total lipids, total cholesterol, triglycerides and LDL-C levels in serum, concomitant with a significant decrease in serum HDL-C. A significant increase in serum AST, ALT, urea and creatinine, while, a significant decrease in total protein content in serum was observ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
26
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 35 publications
(27 citation statements)
references
References 45 publications
1
26
0
Order By: Relevance
“…Many investigators have demonstrated the efficacy of grape seed proanthocyanidins and grape juice as an inhibitor of lipid peroxidation and as a powerful free radical scavenger in vitro and in vivo (Dani et al, 2008;Khalifa et al, 2011;Naguib, 2011) in addition to its hepatoprotective effect (Hassan & Al-Rawi, 2013). Thus it was suggested that the active component of grapes protect the hepatocytes from liver damage and subsequent leakage of enzymes into the circulation, and may have a curative effect against elevated transaminases (Ahmed & Fatani, 2007;Al-Attar, 2015).…”
Section: Discussionmentioning
confidence: 99%
“…Many investigators have demonstrated the efficacy of grape seed proanthocyanidins and grape juice as an inhibitor of lipid peroxidation and as a powerful free radical scavenger in vitro and in vivo (Dani et al, 2008;Khalifa et al, 2011;Naguib, 2011) in addition to its hepatoprotective effect (Hassan & Al-Rawi, 2013). Thus it was suggested that the active component of grapes protect the hepatocytes from liver damage and subsequent leakage of enzymes into the circulation, and may have a curative effect against elevated transaminases (Ahmed & Fatani, 2007;Al-Attar, 2015).…”
Section: Discussionmentioning
confidence: 99%
“…Grape seed extract contains a proanthocyanidin that contains a particularly higher degree of oxygen free radical scavenger potential. It is also thought to increase the good cholesterol, HDL, while decreasing the bad cholesterol, LDL (Hassan & Al-Rawi, 2012).…”
Section: Proanthocyanidinsmentioning
confidence: 99%
“…Hassan et al have provided interesting data in their recent article (Hassan et al 2012). Proanthocyanidins exert significant anti-neoplastic effects in many systemic malignancies.…”
Section: To the Editormentioning
confidence: 99%